2019
DOI: 10.1159/000504891
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Protects Human Retinal Pigment Epithelial Cells from H<sub>2</sub>O<sub>2</sub>-Induced Oxidative Damage via Activation of NRF2 Signaling

Abstract: Aims: Oxidative damage plays a vital role in the pathogenesis of age-related macular degeneration (AMD). Exendin-4 (EX4), a glucagon-like peptide-1 receptor agonist, possesses several pharmacological functions, such as anti-inflammatory and antioxidative properties. However, the effects and mechanism of EX4 on oxidative stress in retinal pigment epithelial (RPE) cells induced by hydrogen peroxide (H 2 O 2) remain unclear. The present study aimed to investigate the protective mechanism of EX4 on human RPE cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Dysfunction and cell death in RPE cells are hallmarks of AMD; mechanistically, oxidative stress and reactive oxygen intermediates are believed to contribute to RPE cell death in AMD [26]. To identify the pathological mechanism of RPE dysfunction in AMD, numerous studies have evaluated RPE cell death in response to oxidative stress using pro-oxidants such as H 2 O 2 and tert-butyl hydroperoxide (tBH) [27][28][29][30]. In the present study, we found that H 2 O 2 led to cytotoxicity above 200 µM in ARPE-19 cells and accompanied apoptotic morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction and cell death in RPE cells are hallmarks of AMD; mechanistically, oxidative stress and reactive oxygen intermediates are believed to contribute to RPE cell death in AMD [26]. To identify the pathological mechanism of RPE dysfunction in AMD, numerous studies have evaluated RPE cell death in response to oxidative stress using pro-oxidants such as H 2 O 2 and tert-butyl hydroperoxide (tBH) [27][28][29][30]. In the present study, we found that H 2 O 2 led to cytotoxicity above 200 µM in ARPE-19 cells and accompanied apoptotic morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Production of ROS and MDA was widely used to reflect the level of oxidative stress; conversely, SOD, which acts as an antioxidant, is essential to decrease the overproduction of ROS and MDA to prevent vascular injury and cell death (Cui et al. 2020 ). OGD induces inflammatory responses and oxidative stress by increasing the levels of TNF-a, IL-1β, IL-6, ROS and MDA and decreasing SOD activity (Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of Keap1/Nrf2/ARE signaling pathway as a druggable target for AMD and other pathologies, various natural and synthetic Nrf2 activators have been recently tested in both in vitro and in vivo studies to evaluate their protective effects against different pro-oxidant stimuli (Pietrucha-Dutczak et al, 2018;Cui et al, 2019;Shao et al, 2019;Zhou et al, 2019;Fresta et al, 2020). In this panorama, our NIHs look as noteworthy pharmacological molecules, displaying a good profile of tolerability ( Figure 3) and uncommon cytoprotective effects in RPE cells under three different types of AMD-related oxidative stress.…”
Section: Discussionmentioning
confidence: 99%